2000
DOI: 10.1108/02644400010339770
|View full text |Cite
|
Sign up to set email alerts
|

Mixed convection heat transfer in ventilated cavities with opposing and assisting flows

Abstract: Mixed convection heat transfer in ventilated cavities submitted to a constant heat flux has been numerically studied using the Navier‐Stokes equations with the Boussinesq approximation. Results in terms of streamlines and isotherms are produced for different values of the governing parameters, namely, the Rayleigh number (103 ≤q Ra ≤q 106) and the Reynolds number (5 ≤q Re ≤q 5, 000). The geometrical parameters are the aspect ratio of the cavity A = L’/H’ = 2 and the relative height of the openings B = h’/H’ = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 9 publications
2
18
0
Order By: Relevance
“…A computational study on mixed convection in a ventilated cavity with uniform heat flux in the left wall was performed by Raji and Hasnaoui [14]. Moreover, Raji and Hasnaoui [15] investigated the mixed convection in ventilated cavities where the horizontal top wall and the vertical left wall were prescribed with equal heat fluxes. Also, Gau et al [16] performed experiments on mixed convection in a horizontal rectangular channel with side heating.…”
Section: Introductionmentioning
confidence: 99%
“…A computational study on mixed convection in a ventilated cavity with uniform heat flux in the left wall was performed by Raji and Hasnaoui [14]. Moreover, Raji and Hasnaoui [15] investigated the mixed convection in ventilated cavities where the horizontal top wall and the vertical left wall were prescribed with equal heat fluxes. Also, Gau et al [16] performed experiments on mixed convection in a horizontal rectangular channel with side heating.…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported in [3] and [4] that flow patterns describe oscillating patterns due to floating forces generated by the heat source, and cooling efficiency improves if the air outlet is located on the lower side of the vertical wall; later in [5], the authors extended the study to an inclined channel, and they concluded that the best behavior on heat transfer is found on vertical channels. Another configurations and heat flux conditions in ventilated cavities were analyzed by Raji and Hasnaoui [6][7][8][9]. On recent works Raji that radiation contributes to the homogenization over temperature distribution and a decrease on the maximum temperature inside the cavity can be observed [9].…”
Section: Introductionmentioning
confidence: 99%
“…In references [13][14][15][16][17][18][19][20][21][22] the authors studied numerically the heat transfer process in ventilated air-cooled cavities for different inlet-outlet opening positions. They found that the increase of the thermal parameters (grand Reynolds number) and the optimal choice of the ventilation orientations can lead to the best cooling effectiveness.…”
Section: Introductionmentioning
confidence: 99%